We flew over the bridge : the memoirs of Faith Ringgold - Ringgold, Faith (Book collections on Project MUSE., 2005)
"In We Flew over the Bridge, one of the country's preeminent African American artists--and award-winning children's book authors--shares the fascinating story of her life. Faith Ringgold's artworks--startling "story quilts," politically charged paintings, and more--hang in the Studio Museum in Harlem, the Metropolitan Museum of Art, the Guggenheim Museum, the Museum of Modern Art, and other major museums around the world, as well as in the private collections of Maya Angelou and Oprah Winfrey. Her children's books, including the Caldecott Honor Book Tar Beach, have sold hundreds of thousands of copies. But Ringgold's path to success has not been easy. In this gorgeously illustrated memoir, she looks back and shares the story of her struggles, growth, and triumphs. Ringgold recollects how she had to surmount a wall of prejudices as she worked to refine her artistic vision and raise a family. At the same time, the story she tells is one of warm family memories and sustaining friendships, community involvement, and hope for the future."--